PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN PT ASIA KARET SENTOSA MEDAN - Amadi, Jam'an (Fakultas Ekonomi Universitas Almuslim Bireuen, 2022)
This research aims to examine the influence of organizational culture, work motivation and work supervision on the performance of PT Asia Karet Sentosa Medan employees. The research method uses quantitative descriptive. The analysis model used is a regression analysis model. The research results show that organizational culture influences employee performance. Likewise, work motivation influences employee performance. Work supervision also influences the performance of PT Asia Karet Sentosa Medan employees. Simultaneously, organizational culture, work motivation and work supervision influence the performance of PT Asia Karet Sentosa Medan employees.